On some properties of the risk function in the generalized “two—armed bandit” problem - Surgailis, D. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Сургайлис. О некоторых свойствах оптимальной цены в обобщенной задаче о двух типах оружияD. Surgailis. Apie kai kurias rizikos funkcijos savybes apibendrintame uždavinyje apie dvi ginklų rūšis